Modelling osteoblast adhesion on surface-engineered biomaterials: optimisation of nanophase grain size. Issue 8 (11th June 2017) - Chen, Song; Lee, Cheuk Y.; Li, Rachel W.; Smith, Paul N.; Qin, Qing H.
Abstract: A double-layered model is proposed for numerically simulating osteoblast adhesion on surface-engineered biomaterials. The proposed model consists of molecular and cellular motions based on theoretical and experimental evidence and creates predictive simulations from sparse experimental data. The comparison of numerical solutions and experimental data reveals that the proposed model can explain the nonlinear behaviour of osteoblast adhesion on material surfaces in respect to nanophase grain size (0–100 nm). The model further provides insight into the optimisation of nanophase grain size on the surface of the biomaterial.